Comparison of Different Maximal Oxygen Uptake Equations to Discriminate the Cardiometabolic Risk in Children and Adolescents (2018)
Objective: To determine the ability of 8 different maximal oxygen uptake (VO 2max ) equations to discriminate between low and high cardiometabolic risk, and to determine cardiorespiratory fitness (CRF) cutoffs associated with a more favorable cardiometabolic risk profile in Colombian children and adolescents. Study design: In a cross-sectional study, CRF was estimated using the 20-m shuttle run test in 2870 schoolchildren (54.5% girls) from Bogota, Colombia. We computed a metabolic syndrome score (MetScore) as the sum of the age- and sex-standardized scores of waist circumference, triglycerides, high-density lipoprotein cholesterol, glucose, and systolic and diastolic blood pressure. Results: Linear regression analyses showed that the Barnett et al (b) and Mahar equations were negatively associated with MetScore, showing the highest discriminatory accuracy for identifying the low/high cardiometabolic risk in both sexes and both age groups (9-12 years and 13-17 years). Conclusions: We propose that the Barnett et al (b) equation for boys and girls, VO 2max = 25.8 × (6.6 × G × 0.2 × (body mass + 3.2 × (final speed))), where G is gender (male = 0; female = 1), be used to classify youths at metabolic risk. The CRF cutoffs can serve as a quantitative marker of a healthier cardiovascular profile in Colombian children and adolescents. © 2017 Elsevier Inc.